CMOS-Based High-Density Silicon Microprobe Arrays for Electronic Depth Control in Intracortical Neural Recording - Seidl, K.; Herwik, S.; Torfs, T.; Neves, H. P.; Paul, O.; Ruther, P. (Journal of microelectromechanical systems, 2011)
This paper reports on a novel high-density CMOS-based silicon microprobe array for intracortical recording applications. In contrast to existing systems, CMOS multiplexing units are integrated directly on the slender, needle-like probe shafts. Single-shaft probes and four-shaft combs have been realized with 188 and 752 electrodes, respectively, with a pitch of 40 μm arranged in two columns along 4-mm-long probe shafts. Rather than performing a mechanical translation of the probe shaft relative to the brain tissue to optimize the distance between electrodes and neurons, the electrode position is adjusted by electronically switching between the different electrodes along the shaft. The paper presents the probe concept, the CMOS circuitry design, the applied post-CMOS fabrication process, and the assembled probe systems.